An Efficient One Pot Four-Component Synthesis of Spiro[indoline-3,4′-pyrano[2,3-c]pyrazole] Derivatives via Electrochemical Approach - Upadhyay, Abhishek; Singh, R.K.P. (Asian Journal of Chemistry, 2021)
An efficient, simple and one pot, synthesis of spiro[indoline-3,4′-pyrano[2,3-c]pyrazole] derivative by electrochemically induced condensation of β-keto ester, hydrazine hydrate, malononitrile or ethyl cyanoacetate and isatin in an undivided cell at constant current where sodium bromide was present as electrolyte in ethanol medium.